From molecular mechanisms to nutritional applications: protein and polyphenol interventions in sarcopenia - Patricia Aragón-Espinosa; Patricia Pérez-Matute; Catherine Bompart; Marine Gueugneau; Frederic Capel; Jose M. Arbones-Mainar; Saioa Gomez-Zorita; Anna Mas-Capdevila; Xavier Escoté; Montserrat Pinent; Anna Ardévol (Journal of Physiology and Biochemistry, 2026)
Sarcopenia, the progressive loss of skeletal muscle mass and function, represents a major public health concern due to its impact on mobility, independence, and quality of life, especially in oldadults. Current treatment strategies primarily rely on resistance training and nutritional support, with particular emphasis on adequate protein intake to stimulate muscle protein synthesis. In this review, we provide an overview of the pathophysiology of sarcopenia, with a focus on the molecular mechanisms underlying muscle atrophy and dysfunction. We explore the role of dietary protein as a cornerstone of sarcopenia management, highlighting current evidence on optimal protein sources and intake strategies. In addition, we examine other nutritional interventions, placing special emphasis on polyphenols, naturally occurring compounds known for their antioxidant and anti-inflammatory properties, which have shown promise in modulating pathways relevant to muscle preservation. Vitamin D and other nutritional supplements are also discussed in the context of their potential to support muscle health. Finally, we address emerging trends in the field, including targeting microbiota. By integrating current findings, this narrative review aims to provide a compilation of the evidence-based nutritional interventions for the prevention and management of sarcopenia.

Effects of dietary camelina oil intake on skeletal muscle metabolism and sarcopenia in older mice - Jean-Paul Rigaudière; Christophe Montaurier; Philippe Denis; Olivier Le Bacquer; Mathieu Rambeau; Chrystèle Jouve; Julia Soullier; Justine Bertrand-Michel; David M. Mutch; Frederic Capel (Journal of Physiology and Biochemistry, 2025)

Eccentric and concentric exercises induce different adaptions in adipose tissue biology - Julianne Touron; Laura Maisonnave; Jean-Paul Rigaudière; Christophe Montaurier; Marie De Antonio; Helene Perrault; Ruddy Richard; Frederic Capel (Journal of Physiology and Biochemistry, 2023)